Compton's by Britannica : Phot-Py. (Chicago : Encyclopedia Britannica, Inc., 2010)
Written and visually designed for students ages 10 to 17, Compton's by Britannica has been thoroughly reviewed, updated, and revised by educators, expert contributors, and Britannica editors. Packed with dramatic pictures, detailed diagrams, and engaging text, Compton's gives young readers the basic facts and entices advanced students to dig deeper for the answers to their more complex questions. Keyed to National Curriculum Standards, Compton's can easily be incorporated by teachers into their lesson plans and used by students to start projects and homework assignments. - Publisher
Arts -- Physical science -- Living things -- Medicine -- Technology and business -- Geography -- History -- Social and political science -- Potpourri.
Keywords: ENCYCLOPEDIAS AND DICTIONARIES